FRI0578 Patient and Clinician Reported Outcomes for Patients with New Presentation of Inflammatory Arthritis: Observations from The UK National Clinical Audit. (15th July 2016) - Ledingham, J.; Snowden, N.; Galloway, J.; Rivett, A.; Firth, J.; Macphie, E.; Kandala, N.; Rowe, I.; Ide, Z.; Dennison, E.; ,
Abstract : Background: Early inflammatory arthritis (EIA) services have undergone substantial reconfiguration in recent years with the recognition of a window of opportunity early on in the disease course as well as the introduction of treat-to-target disease modifying anti-rheumatic drug strategies. As part of a national UK audit into the management of EIA data were collected on patients presenting with inflammatory arthritis for the first 3 months of specialist care. Objectives: Here we report the response to treatment at a national level in terms of clinical outcomes. Methods: All individuals >16 years presenting to specialist rheumatology services in England & Wales with suspected new onset IA were recruited. Clinician & patient derived assessments of outcome were collected with consent at baseline and after 3 months of specialist care. Data collected included the Disease Activity Score (DAS28), the Rheumatoid Arthritis Impact of Disease (RAID) questionnaire (a validated patient reported outcome measure assessing pain; functional capacity; fatigue; physical/ emotional wellbeing; quality of sleep and coping) and impact upon work status. Results: 97% of hospital trusts in England and Wales participated. 6, 354 patients with suspected early inflammatory arthritis were recruited between 1st February 2014 to 31st January 2015. Of these 2896 were diagnosed with RA (defined by the presence of polyarticular disease (>5 joints involved) or pauciarticular disease with positive cyclic citrullinated peptide antibody); this represented >40% of estimated expected incident RA cases. At first specialist assessment DAS28 was reported for 91% of RA patients: mean DAS28 was 5.0 (44% of patients a DAS28>5.1 indicating severe disease). The mean RAID score was 5.6 (range 0 not affected to 10 (most affected). After 3 months of specialist care mean DAS28 reduced to 3.5 with 62% achieving a meaningful reduction in DAS28 of >1.2 units. 24% of patients achieved DAS remission. The mean RAID score after 3 months was 3.6; the mean reduction in RAID score was 2.6 and did not meet the minimum clinically important level of 3. Of the working patients aged 16–65 years providing data 7%, 5%, 16% and 37% reported that they were unable to work, needed frequent time off work, occasionally and rarely needed time off work due to their arthritis respectively. 19% reported never being asked about their work by clinicians. Conclusions: Although there are data that suggest the severity of RA has diminished in recent years, this audit confirms that at presentation RA remains a disease with significant patient burden. Acknowledging that this audit only captures the first 3 months of care, the results demonstrate important achievements in RA care in contrast to what might have been expected for RA in previous decades. However, less than a quarter of patients achieved remission and improvements in RAID scores were below the accepted minimum clinically important difference within the first 3 months. Disclosure of Interest: None declared